2008
DOI: 10.1016/j.niox.2008.06.221
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effect of nitric oxide on the rabbit bladder after ovariectomy

Abstract: Ovariectomy resulted in decreased blood flow and hypoxia to the bladder mucosa and smooth muscle. Nitric oxide (NO) played an important role in regulating bladder function during bladder ischemia and reperfusion. This study was designed to evaluate the role of NO on bladder function in the first few days after ovariectomy. Female rabbits were separated into three groups, one which received no medication, pre-medicated with N(omega) -nitro-L-arginine methyl ester (L-NAME) and the third treated with L-arginine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…An initial resting tension of 2 g was applied for 30 min, and contractile responses were recorded isometrically using a force-displacement transducer. The maximal response was determined sequentially for electrical field stimulation (EFS; 2, 8, and 32 Hz), carbachol (20 M), and KCl (120 mM) (32).…”
Section: Methodsmentioning
confidence: 99%
“…An initial resting tension of 2 g was applied for 30 min, and contractile responses were recorded isometrically using a force-displacement transducer. The maximal response was determined sequentially for electrical field stimulation (EFS; 2, 8, and 32 Hz), carbachol (20 M), and KCl (120 mM) (32).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous described [ 60 , 89 , 90 , 91 ], the bladders were recorded for weight and cut into three longitudinal strips measuring 0.5 × 1.5 cm 2 from the bladder dome to the trigone area. Contractile responses were performed using a force-displacement transducer.…”
Section: Methodsmentioning
confidence: 99%
“…11 Previous studies in rabbits showed that ovariectomy causes decreased serum estrogen, decreased urothelial oxygenation and blood flow, ischemia, oxidative stress, hypoxia, decreased contractile responses, increased collagen, decreased free fatty acids and phospholipids and urothelial apoptosis. 11,12 In rat models, ovariectomy caused oxidative stress and unstable vesicular and urethral pressures. 13 Male rabbit models, which showed similar ischemic conditions displayed a clear increase in the oxidation of all subcellular components of the bladder tissue during obstruction.…”
Section: Introductionmentioning
confidence: 99%